P02-357 - In vivo molecular imaging reveals distinct distributions of the serotonin transporter, the major inhibitory and excitatory serotonin receptors - Savli, M.; Bauer, A.; Häusler, D.; Kroll, T.; Hahn, A.; Rattay, F.; Mitterhauser, M.; Wadsak, W.; Kasper, S.; Lanzenberger, R. (European psychiatry, 2011)
Based on evidences in molecular neuroimaging, postmortem and genetic studies, impaired serotonergic neurotransmission has been implicated with affective disorders. Moreover, a growing number of evidences showed strong interrelations within the serotonergic system suggesting a common mechanism in the modulation of receptor and transporter densities. Here we directly investigated the regional expression of the 5-HT 1A, 5-HT 2A and 5-HTT using PET and the three highly selective and specific radioligands [carbonyl- 11C]WAY-100635, [ 18F]Altanserin and [ 11C]DASB in healthy subjects. A total of 55 healthy subjects (5-HT 1A: 36 subjects, 18 males, age = 26.0 ± 4.9; 5-HT 2A: 19 subjects, 11 males, age = 28.2 ± 5.9; 5-HTT: 8 males, age = 28.12 ± 3.6) were included in this study. Binding potential (BP ND) values were quantified according to the AAL parcellation scheme. BP ND values averaged over both hemispheres ranged from 0.40–6.35 for the 5-HT 1A receptor; 0.01–2.01 for the 5-HT 2A receptor and 0.09–2.05 for the 5-HTT, respectively. There was a specific topological pattern according to the ratio between the 5-HT 1A, 5-HT 2A receptors and 5-HTT (“fingerprints”). Such information can be essential for detecting potential local alterations in the ratio between different binding proteins on a network level in pathological conditions. Moreover, these data might provide further insight in area-specific effects of frequently prescribed selective serotonin re-uptake inhibitors (SSRI): 1) due to the distinct local receptor and transporter availability; 2) SSRI application alters the postsynaptic receptor expression and thus; 3) leads to a modified interaction of inhibitory and exhibitory receptors.